A Critical Review on Universal Grammar of Chomsky in Learning a Second language - Abbas, Tasawar; Ghulam Yaseen, Hafiz (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
As many scholars have their own viewpoints and perspectives on Chomsky's universal grammar theory, this article shows recent developments in L2 learning by Chomsky. A significant turning point at the moment is Chomsky's UG approach to language education, particularly its values and parameters. Many researchers argue that with SLA, UG has problems like Fries and Palmer. They say that there are linguistic variations that make it difficult to differentiate between the SLA and the first language acquisition. It is possible to further clarify what would be specifically based on in future linguistic studies by assessing the challenges, so that development will be advanced towards language learning and SLA.